Harmful marine dinoflagellates (Dinophyceae) of Malaysia including new records of taxa based on morphology and molecular - Tan, Toh Hii (Universiti Malaysia Sarawak (UNIMAS), 2012)
Dinoflagellates are eukaryotic biflagellated, unicellular organisms that can be found ,in both freshwater and marine habitats. Several species are harmful as they produce potent neurotoxins; cause unusual blooming phenomena in the marine environment. In Malaysia, harmful algal blooms (HABs) event was first reported in 1976. Since then several studies on HABs have been undertaken, focusing mainly in areas where poisoning cases were reported.) In this study, samplings were conducted in several locations including sites where' no poisoning case has been reported, but intensive aquaculture activity is ongoing. Plankton and seaweed samples were collected and brought back to the laboratory. Single-cell of dinoflagellates were isolated and clonal cultures established. Both field and cultured specimens were observed under light and scanning electron microscopy (SEM). Identification to species level was based on detailed investigation of the thecal plates. Nucleotide sequences of the nuclearencoded ribosomal DNA were obtained from clonal cultures, and preliminary toxin analysis was performed by ELISA and LC-MS. A total of 46 taxa of harmful and/or potentially harmful dinoflagellates were identified and documented from four locations (Cherating, Pahang, Port Dickson, Negeri Sembi lan, Tebrau Strait, Johor, and Kuching, Sarawak). Two taxa are new records of occurrence in Malaysian waters, namely Karlodinium veneficum from Tebrau Strait and Protoceratiumfukuyoii sp. nov from Semariang. Notably the PST-producing dinoflagellates, Alexandrium lamiyavanichii and Pyrodinium bahamense were found, for the first time, in Sarawak waters and the Straits of Malacca, respectively. Molecular data obtained from the present study, and the molecular signatures identified for each species will serve as preliminary data for DNA barcoding of the harmful dinoflagellates. Inventory of the harmful dinoflagellate species wiIl provide useful baseline infonnation of the harmful species present in Malaysian waters. Furthermore, distribution data on harmful dinoflagellates could be used to identify the hotspots of potential HABs incidences for early warning and HABs monitoring purposes.